Relationship of Motivation to Be a Nurse with Learning Achievement - Suprapto Suprapto; Andi Abdul Malik; Yuriatson Yuriatson (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Academic achievement is the last learning achievement achieved by students in a certain period of time in which student academic achievement is usually expressed in the form of numbers or symbols. The purpose of this study was to determine the relationship between motivation to be a nurse and student achievementat the Sandi Karsa Nursing Academy. Research method descriptive-analytic using a cross-sectional approach, analyzing the relationship between motivation to be a nurse and academic achievement of the Nursing Academy Sandi Karsa Makassar students. The results of the study with Chi-Square with a significance level (α) = 0, 05. p-value = 0.046 p <α was obtained. This means that there is a relationship between motivation to become a nurse and student achievement at the Sandi Karsa Nursing Academy. Conclusion there is a very close relationship between motivation and learning achievement, it is expected that students to maintain motivation to be nurses who are already high as a driver to improve learning achievement and educational institutions in order to motivate and introduce the role of nurses in health and work prospects that are quite promising for the future.